1983
DOI: 10.2165/00003088-198308010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Systemic Antifungal Drugs

Abstract: The currently available drugs for the treatment of systemic fungal infections are amphotericin B. flucytosine. miconazole and ketoconazole.Amphotericin B has to be given intravenously in the treatment of deep mycoses. The dose is gradually increased following a small initial dose. though this may delay the attail/menl of therapeutic concentrations. Amphotericin B. serum concentrations are proportiol/al to dose but only up to doses of 50mg. The serum pharmacokinetics fit a 3-compartment model. while cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(83 citation statements)
references
References 130 publications
0
82
0
1
Order By: Relevance
“…Glucuronidation has not been reported for this drug and this could explain the lack of interaction. However, we also demonstrated that miconazole is a strong inhibitor of ZDV glucuronidation and glucuronides have not been described for this drug [16]. Miconazole could therefore interact with UGT by an unknown mechanism (formation of inactive complex, steric hindrance, physical or chemical perturbation of the microsomal membrane, etc).…”
Section: Resultsmentioning
confidence: 78%
“…Glucuronidation has not been reported for this drug and this could explain the lack of interaction. However, we also demonstrated that miconazole is a strong inhibitor of ZDV glucuronidation and glucuronides have not been described for this drug [16]. Miconazole could therefore interact with UGT by an unknown mechanism (formation of inactive complex, steric hindrance, physical or chemical perturbation of the microsomal membrane, etc).…”
Section: Resultsmentioning
confidence: 78%
“…This is in contrast to the imidazole antifungal agents, including ketoconazole, in which plasma protein binding is typically in excess of 98% (4). This 40-to 50-fold difference in unbound fractions of UK-49,858 and ketoconazole in plasma is likely to be a significant contributory factor to the 20-to 100-fold potency advantage of UK-49,858 in vivo over ketoconazole (14; Troke et al, submitted).…”
Section: Methodsmentioning
confidence: 99%
“…Peak concentrations in plasma of drug normalized to a 1-mg/kg dose level following oral administration, were relatively high: 0.7, 0.6, 1.1, and 1. 4 ,ug/ml in mice, rats, dogs, and humans, respectively. The volumes of distribution ranged between 1.1 liter/kg in mice and 0.7 liter/kg in humans, which are approximate to the values for total body water.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…. Dosage could well be an important factor since there is evidence of dose-dependant kinetics for ketoconazole (Daneshmend & Warnock, 1983) and thus the potential exists for non-linear accumulation of drug with increasing dose and disproportionate effects on steroid synthesis. Preliminary data suggests that plasma cortisol concentrations may be greatly depressed throughout the day in occasional patients taking high doses of ketoconazole (Pont et al, 1983) although only one case has been reported of a patient receiving ketoconazole manifesting hypoadrenalism (discussed by Pont et al, 1984).…”
Section: Resultsmentioning
confidence: 99%